Muro-ami - Jimenez, Butch; Duavit, Jimmy; Diaz-Abaya, Marilou; Jimenez, Menardo R.; Duavit, Gilberto M.; Gozon, Felipe L.; Montano, Cesar; Medina, Pen; Hilario, Jhong; Austria, Amy; Abaya, Leo; Lacap, Rody; et al. (GMA Network Film, 1999)
Maestro Fredo, a tyrant captain, fixates to claim the treasures of the sea -- no matter what, in whatever diabolical technique for as long as he profits. He employs dozens of men, mostly children, in his dangerous expeditions. Conditions aboard the ships are oppressive. Children are often overworked and his crew is furious with the way they are living. He blames the sea for claiming the lives of his family and he exacts revenge by plundering its depths.